Unsupported shaped cobalt nanoparticles as efficient and recyclable catalysts for the solvent-free acceptorless dehydrogenation of alcohols. Issue 2 (20th December 2017) - Viola, Arnaud; Peron, Jennifer; Kazmierczak, Kamila; Giraud, Marion; Michel, Carine; Sicard, Lorette; Perret, Noémie; Beaunier, Patricia; Sicard, Mickaël; Besson, Michèle; Piquemal, Jean-Yves
Abstract : Unsupported cobalt nanoparticles are active and chemoselective catalysts for the solvent-free acceptorless dehydrogenation of alcohols. Abstract : Oxidation of alcohols is a key-reaction for the valorization of biomass compounds, and green processes are preferred to avoid the use or production of toxic compounds. In this context, unsupported nanometer-sized catalysts have emerged as very promising materials for heterogeneous catalysis. In this paper we explore the catalytic activity of unsupported cobalt nanoparticles towards the dehydrogenation of aliphatic primary and secondary alcohols under solvent-free conditions. The unsupported particles are found to be highly active for the conversion of secondary alcohol to the corresponding ketone vs. the primary alcohol. The oxidation process is following an acceptorless dehydrogenation mechanism, where the only by-product of the reaction is the highly valuable H2 molecule. DFT calculations evidence that the chemoselectivity of secondary vs. primary alcohols originates from a more favorable desorption of the ketone reaction product compared to the aldehyde. It is also found that the morphology of the particles has a strong influence on the catalyst efficiency and stability: Co nanorods can be recycled at least three times without a loss in catalytic performances.